The Double Dip: How Tropospheric Expansion Counteracts Increases in Extratropical Stratospheric Ozone Under Global Warming - Aaron Match; Edwin P. Gerber (Geophysical Research Letters)
Abstract In response to rising CO2, chemistry‐climate models (CCMs) project that extratropical stratospheric ozone will increase, except around 10 and 17 km. We call the muted increases or reductions at these altitudes the “double dip.” The double dip results from surface warming (not stratospheric cooling). Using an idealized photochemical‐transport model, surface warming is found to produce the double dip via tropospheric expansion, which converts ozone‐rich stratospheric air into ozone‐poor tropospheric air. The lower dip results from expansion of the extratropical troposphere, as previously understood. The upper dip results from expansion of the tropical troposphere, low‐ozone anomalies from which are then transported into the extratropics. Large seasonality in the double dip in CCMs can be explained, at least in part, by seasonality in the stratospheric overturning circulation. The remote effects of the tropical tropopause on extratropical ozone complicate the use of (local) tropopause‐following coordinates to remove the effects of global warming.